The Impact of Mobile Money, Quick Response Codes, and Financial Inclusion on the Performance of Micro, Small, and Medium Enterprises (MSMEs) Moderated by Dynamic Capability (Case Study of Women-Owned MSMEs in Kendari City) (Architecture Image Studies, 2026)
This study aims to analyze the influence of Mobile Money, Quick Response Code, and Financial Inclusion on the performance of women-owned Micro, Small, and Medium Enterprises (MSMEs) in Kendari City, and to examine the role of Dynamic Capability as a moderating variable. A quantitative approach was used in this study using the Partial Least Square (PLS) analysis method, based on data collected through questionnaires. This study used the SEM PLS analysis technique with a sample of 396 people. The results showed that the three independent variables had a positive and significant effect on MSME performance. The adoption of digital financial services and access to financial facilities have been shown to encourage operational efficiency, strengthen financial management, and increase business competitiveness. Dynamic Capability plays a role in strengthening this influence, where the ability of business actors to adapt, innovate, and manage resources responsively has an additional impact on improving business performance. These findings emphasize the importance of strengthening the internal capacity of MSMEs in utilizing financial technology to achieve sustainable growth, especially for women entrepreneurs.